A study on how freelance remote working affects work-life balance and its implication for employment options - Advento, Marelle Joy T.; Cada, Shiela N.; Catindoy, Richel L.; Quiros, Glynness A.
Numerous studies have explored the impact of remote work on work-life balance; however, there has been a research gap regarding its localized context here in Eastern Visayas. Additionally, only a few studies have explored exclusively online freelance work. and little to no data has been recorded on its implications for current employment opportunities or alternatives. This research has examined the impact of freelance work on work-life balance through a percentage and ratio analysis of a 50-item Likert questionnaire that has covered commonly identified dimensions of work-life balance. The results have shown that all identified dimensions- personal time, psychological well-being, social relationships, productivity, and career development are positively impacted by freelance remote working, with reservations in terms of career trajectory or growth. Through a thorough examination of these dimensions, the study has also identified key factors freelancers have prioritized for work-life balance: rest periods for personal time, resources and competence for psychological well-being, family engagement for social relationships, efficient task management for productivity, and career exploration with geographic flexibility for career development. These observations have implied that freelance remote working has been considered a relatively good employment option for supporting individuals' work-life balance. Therefore, the findings of this research have been expected to help businesses, the government, and aspiring freelancers find guidance and relevant insights about freelance remote working and work-life balance.